EFFORTS TO IMPROVE PHYSICAL EDUCATION LEARNING ON PHYSICAL FITNESS MATERIAL THROUGH GAME BASED LEARNING FOR GRADE XI STUDENTS OF SMA NEGERI 7 BANDA ACEH - Turia Ningsih; Nasrullah; Wahid; Muhajir (CV. Asry Persada Quality, 2025)
Physical Education is a subject that aims to improve students' physical fitness through various physical activities. One of the important materials in learning Physical Education is physical fitness. However, many students are less interested and feel less motivated in following the material. One effort to overcome this is to implement game-based learning. Game-based learning not only makes students more interested and actively involved, but can also improve physical fitness effectively. This article aims to explain efforts that can be made to improve physical fitness learning through a game-based learning approach for class XI students of SMA Negeri 7 Banda Aceh. Game-based learning can create a fun and challenging atmosphere, as well as improve students' teamwork and social skills. By adapting games that are relevant to the objectives of learning physical fitness, students can benefit both physically and socially. Constructive evaluation and feedback are also very important to support student development. It is hoped that with this approach, physical education learning can be more effective and enjoyable.